Instrumentalism and the publish-or-perish regime - Becker Albrecht; Lukka Kari (Elsevier (Commercial Publisher), 2023)
in the academe, we firstly examine based on which perceptions and interpretations individual
researchers at universities cope with, survive, or even flourish, in the context of the publish-orperish
regime. Secondly, we probe, following a critical agenda of fostering non-instrumentalist
understandings of research, to which extent local conditions may impact these perceptions, interpretations,
and ways of coping. We conducted interviews with 32 researchers from six different
research units in European universities across all ranks of the academic hierarchy, from first-year
PhD students to very senior professors. Our focal descriptive category is instrumentalism: the
degree to which an instrumentally rational understanding of research as a means of producing
publications as items of countable performance dominates the entire research process from its
very beginning. In our study we find notably heterogeneous forms of instrumentalism, which we
have termed modes of instrumentalism, from purposely instrumentalist to critical noninstrumentalist
modes. We identify and describe local research cultures as mediating the perceptions
of individual researchers, and thus the influence of the global publish-or-perish regime
on them. Based on our conceptualisation of degrees and modes of instrumentalism and the local
research cultures we sketch some measures for fostering non-instrumentalist research cultures
that would help in resisting the undesirable effects of the publish or perish regime.